Crystallization and preliminary X‐ray diffraction analysis of the amidase domain of allophanate hydrolase from Pseudomonas sp. strain ADP. Issue 3 (1st March 2014) - Balotra, Sahil; Newman, Janet; French, Nigel G.; Briggs, Lyndall J.; Peat, Thomas S.; Scott, Colin
<x xml:space="preserve">Abstract</x> The allophanate hydrolase from Pseudomonas sp. strain ADP was expressed and purified, and a tryptic digest fragment was subsequently identified, expressed and purified. This 50 kDa construct retained amidase activity and was crystallized. The crystals diffracted to 2.5 Å resolution and adopted space group P21, with unit‐cell parameters a = 82.4, b = 179.2, c = 112.6 Å, β = 106.6°.